An uncommon presentation of a common disease: a case of tertiary syphilis - Bhat, Manjari; Hamza, Ashique; S., Subin; Kumar, K. G. Sajeeth (International Journal of Advances in Medicine, 2021)
Thoracic aortic aneurysm is one of the late and uncommon presentations of syphilis. If the aneurysm is large it causes symptoms suggesting mass effect. Syphilis being a common disease worldwide has recently re-emerged. Early syphilis if left untreated can lead to a significant morbidity. We reported a case of 44 years old man who was incidentally detected to have syphilitic thoracic aortic aneurysm with features of SVC compression.